2014
DOI: 10.9734/bjpr/2014/12232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Extraction Techniques of Persicaria odorata Extracts Utilizing Anti-bacterial Bioassay

Abstract: Persicaria odorata is a common plant and well known in Malaysia as "Daun kesum" that is commonly used in cuisines and has various medicinal properties. This study was conducted to investigate the antimicrobial activity and the extraction technique that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…It is a distinct process from reading comprehension in that it involves comprehending spoken language. Recognizing speech sounds, grasping the meaning of individual words, and understanding the grammar of sentences are examples of these abilities [14,15]. According to Hamouda [16], listening comprehension refers to comprehending what the listener has just heard.…”
Section: Introductionmentioning
confidence: 99%
“…It is a distinct process from reading comprehension in that it involves comprehending spoken language. Recognizing speech sounds, grasping the meaning of individual words, and understanding the grammar of sentences are examples of these abilities [14,15]. According to Hamouda [16], listening comprehension refers to comprehending what the listener has just heard.…”
Section: Introductionmentioning
confidence: 99%
“…formosum and P. odoratum have good chemical compounds such as phenols, alkaloids, flavonoids, xanthones, tannin, and terpenoids, previous studies have reported that these plants have high potential against bacteria. ,,, As a result, they were chosen to explore their antibacterial efficiencies on S. aureus and E.…”
Section: Introductionmentioning
confidence: 99%
“…aureus and E. coli by the disk diffusion method. ,, However, no study has been applied extraction of C. formosum and P.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each experiment was carried out in triplicate. The zones of inhibition were then recorded in millimeters 11,12 .…”
Section: Bio-efficacy Testmentioning
confidence: 99%